2018
DOI: 10.1080/2162402x.2018.1445457
|View full text |Cite
|
Sign up to set email alerts
|

Optimized dendritic cell vaccination induces potent CD8 T cell responses and anti-tumor effects in transgenic mouse melanoma models

Abstract: Despite melanoma immunogenicity and remarkable therapeutic effects of negative immune checkpoint inhibitors, a significant fraction of patients does not respond to current treatments. This could be due to limitations in tumor immunogenicity and profound immunosuppression in the melanoma microenvironment. Moreover, insufficient tumor antigen processing and presentation by dendritic cells (DC) may hamper the development of tumor-specific T cells. Using two genetically engineered mouse melanoma models ( and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…So, blockage of immunosuppressive function of TME may enhance effecacy of CART‐19 cells. Certain studies support our hypothesis, anti‐PD‐L1 could augment the antitumor activity of tumor‐directed immunocytes in inhibiting tumor growth . Schuster et al reported a refractory DLBCL patient of primary mediastinal origin with extra‐nodal involvement of small intestine.…”
Section: Discussionsupporting
confidence: 73%
“…So, blockage of immunosuppressive function of TME may enhance effecacy of CART‐19 cells. Certain studies support our hypothesis, anti‐PD‐L1 could augment the antitumor activity of tumor‐directed immunocytes in inhibiting tumor growth . Schuster et al reported a refractory DLBCL patient of primary mediastinal origin with extra‐nodal involvement of small intestine.…”
Section: Discussionsupporting
confidence: 73%
“…DC1 cells in the skin draining lymph nodes, tumors, and intestines express high levels of CD103 whereas DC1 cells in the spleen have low or undetectable levels (24)(25)(26)(27)(28). The CD8 + subset of DCs has been reported to be more potent than the CD8subset in crosspresenting cell associated protein antigens to conventional CD8 + T cells, and selective depletion of the CD8+ subset markedly attenuates CD8+ T cell immunity to tumors and viruses by virtue of cross antigen presentation (29)(30)(31)(32). CD8 + DCs take up proteins from exogenous cell sources that are the source of the antigens, such as tumor cells and viral infected cells, process the proteins such that the derived peptides are crosspresented to CD8 + T cells after association with MHC receptors on the cell surface (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these results imply that IL‐10 released from melanoma cells suppresses the tumor‐infiltrating DC . Several animal models showed that DC vaccine enhanced the effect of immune checkpoint inhibitors . Therefore, we think DC may play important roles in the antitumor effect of immune checkpoint inhibitors, and dysfunction of the tumor‐infiltrating DC may attenuate the effect of it.…”
Section: Discussionmentioning
confidence: 81%
“…17 Several animal models showed that DC vaccine enhanced the effect of immune checkpoint inhibitors. 18 Therefore, we think DC may play important roles in the antitumor effect of immune checkpoint inhibitors, and dysfunction of the tumor-infiltrating DC may attenuate the effect of it. Taken together, our results indicate that the acquisition of resistance to BRAF inhibitors is unfavorable for immune checkpoint inhibitors if the patients plan to receive them after receiving BRAF inhibitors.…”
Section: Discussionmentioning
confidence: 99%